Ambulance tracking system with global system for mobile and global positioning system - G. , Saicharith; R. , Puviarasi (International Journal of Psychosocial Rehabilitation, 2020)
Normally, an ambulance is a vehicle concept that is made to help suffering people who face health situations. Ambulance is used to move patients quickly at critical care in emergency situations Generally,IOTplays a vital role in figure students and researchers One of the main applications of IoT is the ambulance trailing system; it consists of GPS , antenna, GSM module and ATMega microcontroller . during this user location is located out by the GPS system, this platform supports innovation in trendy technology The system projected within the current work combines GPS and GSM services for trailing the situation and position of the vehicles for secured functions. The GPS satellite is accountable forgetting the coordinates of the vehicle. The Vehicle chase System offered by United States of America is GPS-primarily based and is most typically used transportation service suppliers for fleet management. VTS conjointly finds application in client application as a felony interference & retrieval device. IN case of felony, police will simply trace the taken vehicle’s location by merely following the GPS path that is shown on-line by a chase system. A vehicle chase system uses automatic vehicle location of individual vehicles together with the computer code that helps in collection of fleet information for a comprehensive image of the placement of a vehicle.